Hubungan Pengetahuan Dan Sikap Remaja Tentang Perilaku Seksual Pra Nikah Pada Mahasiswa Stikes Pemkab Jombang - Rodiyah Rodiyah; Erika Agung Mulyaningsih; I'in Noviana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: The Purpose of this study is to determine the correlation of attitude and knowledge of adolescent about premarital sexual behavior in students of Stikes Pemkab Jombang.. Methods: The study design used analytic correlational with cross sectional approach. The populations were all undergraduate nursing students level 1 and 2 aged between 17 to 21 years (late adolescence) and as many as 154 unmarried students. Sampling used a total sampling technique as many as 154 respondents. The independent variable was knowledge about pre-sexual behavior marriage and the dependent variable is attitudes about premarital sexual behavior. Data was taken using a questionnaire via google form. Data analysis used the chi square test with = 0.05. Results: From this study, it was found that almost all of the knowledge of adolescents (91.6%) were in the good category, most (63.6%) of adolescents had a positive attitude. Statistical tests with Chi-Square Tests get the results = 0.000 < = 0.05 or ( < ). This means that there is a correlation between the knowledge and adolescents attitudes about sexual behavior of Premarital in students of Stikes Pemkab Jombang.Conclusion: Good knowledge will have an impact on adolescents' attitudes about pre-marital sexual behavior where the higher the knowledge, the positive attitudes of adolescents towards pre-marital sexual behavior. One of the prevention of premarital sexual behavior is that students are expected to strengthen their faith, participate in meaningful activities and establish good communication with parents.